The Divergent Paths of Behavior Analysis and Psychology: Vive la Différence! - Thyer, Bruce A. (Behav Anal, 2014)
Twenty years ago I suggested that behavior analysts could effect a quiet and covert takeover of the American Psychological Association (APA). I gave as precedents the operation of similar initiatives in the nineteenth and twentieth centuries, the Darwinian-inspired X-Club, and the psychoanalytically-oriented Secret Ring. Though a conscientious program of working within established APA bylaws and rules, behavior analysts could ensure that behavior analysts were nominated for every significant elective position within the APA, and move to get their colleagues placed in appointive positions, such as journal editorships, review boards, and major committees. This would be one approach to remake psychology along behavioral lines, which was an early ambition of B. F. Skinner. The community of behavior analysts ignored my suggestion, and instead pursued the path of creating an independent discipline of practitioners, one with its own degree-granting programs, conventions, journals, and legal regulation. This effort has been immensely successful, although much critical work remains to be done. In retrospect, I was wrong to suggest changing psychology from within, and I have been delighted to witness the emergence of our new and independent field.